And I am telling you... lesbiyana ako a textual analysis of Charice Pempengco's representation as she comes out of the closet on Philippine TV - Angeles, Eleonor Joy Sabater 1992-; Enriquez, Elizabeth L.; University of the Philippine Diliman. College of Mass Communication (2014)
"This study is about the representation of Charice Pempengco as she comes out of her closet as a lesbian on Philippine Television. It seeks to identify how Charice is represented through news and current affairs and other talk programs featuring her coming out on Philippine free television. It also seeks to discover how I see myself as a lesbian who is in the process of fully coming out, especially to my parents. This thesis is more than just a thesis. To me, it serves as a means of coming out to the world; like what Charice courageously did on national television and to her mother on a personal level. Judith Butler's Queer Theory and Stuart Hall's notion of Representation are used in order to identify the portrayals of Charice as a lesbian. I have classified these portrayals into three: The Lesbian Celebrity, The Lesbian Lover, and The Lesbian Daughter. To give an in-depth discussion of Charice's representation s a lesbian, self-ethnography will also be employed. My personal narrative shall be used in order to analyze and compare Charice's representation after coming out and how I represent myself in my quest for freedom. Thus, this thesis intends to show the parallels of Charice Pempengco's coming out as seen on television to my own experience as a lesbian who is still in the process of coming out."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Charice, 1992--in mass media; Gender expression